Historical and comparative perspectives on trade union regulation with specific emphasis on the accountability of trade unions to their members - Greenhalgh, Bradley Paul (Stellenbosch : Stellenbosch University, 2020)
Thesis (LLD)--Stellenbosch University, 2020.